The impact of temperature, slice thickness and pretreatment solution on convective drying and rehydration capacity of radish slices - Doymaz, Ibrahim (TAYLOR & FRANCIS INC, 2025)
This study investigated the effect of air temperature, slice thickness and pretreatment solution on the drying time and rehydration capacity of radish slices. Radish slices were first treated with a solution of citric acid and then dried in a cabinet dryer at different temperatures. In addition, some samples were dried at same temperatures without being immersed in any solution. Four mathematical models were evaluated in the kinetic study. The model of Aghbashlo et al. showed a better fit to the experimental data compared to other models. Moisture transfer through radish slices was characterized using Fick's second diffusion model. It was found that the effective moisture diffusivity (Deff) values ranged from 2.958 x 10-10 to 8.029 x 10-10 m2/s. In comparison to the other samples, the samples that had been pretreated with citric acid solution had higher Deff values. The activation energies of the citric acid and control samples were found to be 22.55 kJ/mol and 29.01 kJ/mol, respectively. The highest rehydration capacity was found to be 7.079 kg/kg in citric acid coded radish slices dried at 40 degrees C.
Keywords: Drying; effective moisture diffusivity; mathematical modeling; pretreatment solution; radish slices; rehydration; KINETICS; L.; Engineering